2016
DOI: 10.1007/s13361-016-1501-2
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantification of Rifampicin by MALDI Imaging Mass Spectrometry Using Multiple TOF/TOF Events in a Single Laser Shot

Abstract: Matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI IMS) allows for the visualization of molecular distributions within tissue sections. While providing excellent molecular specificity and spatial information, absolute quantification by MALDI IMS remains challenging. Especially in the low molecular weight region of the spectrum, analysis is complicated by matrix interferences and ionization suppression. Though tandem mass spectrometry (MS/MS) can be used to ensure chemical specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…40 This instrument is equipped with a 349 nm, diode-pumped, frequency-tripled Nd:YLF laser capable of laser repetition rates up to 5 kHz (Spectra-Physics, Santa Clara, CA). The laser energy for all experiments was ~66 μ J/pulse (as measured prior to attenuation).…”
Section: Methodsmentioning
confidence: 99%
“…40 This instrument is equipped with a 349 nm, diode-pumped, frequency-tripled Nd:YLF laser capable of laser repetition rates up to 5 kHz (Spectra-Physics, Santa Clara, CA). The laser energy for all experiments was ~66 μ J/pulse (as measured prior to attenuation).…”
Section: Methodsmentioning
confidence: 99%
“…Over the last decade the analytical sensitivity 9 and the acquisition speed 10 for MALDI MSI instruments improved dramatically. As a consequence, new fields of application for MALDI MSI evolved in chemistry 11,12 , biology 13 , medicine 14 and life sciences 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…One approach could concern the normalisation strategy to adopt. Over the past year, the normalisation to a stable isotope internal standard has been shown to increase the quantitative capabilities of MSI analysis (Pirman and Yost, 2011;Prentice, Chumbley and Caprioli, 2017). In this study, in the absence of an internal standard, the MSI data were normalised to total ion current (TIC).…”
Section: Effect Of the Penetration Enhancer Dmi On Levels Of Terbinafmentioning
confidence: 99%
“…Multiple studies have shown how normalisation to an internal standard increases the quantitative capabilities of MSI analysis (Pirman and Yost, 2011;Prentice, Chumbley and Caprioli, 2017). The internal standard is a molecule with chemical and physical characteristics similar to analytes under study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation